Aus der Welt gefallen : Die Geographie der Verschollenen - Kuhn, Kristina; Struck, Wolfgang (2019)
Drawing from the archive of the Perthes publishing house, this study reconstructs how cast away explorers shaped not only the literary imagination but also the history of cartography. Petermanns Geographische Mitteilungen, one of the most prestigious geographical journals in 19th century Europe, extensively propel the stories of those who got lost in the process of exploration.